Knowledge, Attitude and Practices in Type 2 Diabetes Mellitus Patients in Rural Northern India - Gupta, Rajiv Kumar; Shora, Tajali N; Jan, Rayaz; Raina, Sunil Kumar; Mengi, Vijay; Khajuria, Vijay (Indian Journal of Community Health, 2015)
Background: - Type 2 Diabetes Mellitus (T2DM) is a leading cause of morbidity and mortality. Generating awareness on prevention of Diabetes is of key importance. For generating awareness, an idea on the level of awareness in general population has to be generated. The present study was conducted with the aim to assess Knowledge, Attitude and Practices (KAP ) among diabetic patients from a rural area. Methods:- The study was conducted on diagnosed cases of T2 DM patients visiting Community Health Centre, Ranbir Singh Pura, Jammu, J&K for a follow-up. The study was conducted from October through December 2014 using a pre designed, pre-structured & validated questionnaire. Results: - 230 T2 DM patients comprising 128 males and 102 females were enrolled during the study period. The knowledge score of the patients was found to be 10.13±2.09, attitude score was 3.13±1.26 and practice score was 2.86±1.39 out of maximum possible scores of 14,6 and 5 for knowledge, attitude and practices respectively. Knowledge scores had a strong association both with attitude as well as practice scores (p<0.05). Conclusions: - Knowledge of diabetic patients was good but attitude and practices needed improvement.